When a weed can be a crop - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1997)
Women farmers across Africa have developed techniques for managing plant species that, under certain circumstances, could be perceived as weeds. For example, once established in the soil cocoyam tubers will sprout rapidly and compete vigorously...